THE ROLE OF EUROPEAN INTEGRATION IN INNOVATION MANAGEMENT IN HIGHER EDUCATION - Наталя Тесленко (Економіка та суспільство, 2023)
This article delves into the strategic imperative for Ukrainian higher education institutions (HEIs) to align with the European Education Area (EEA), a process underscored by the Ukrainian Strategy for the Development of Higher Education for 2022-2032. The integration into the EEA promises manifold advantages for Ukrainian education, economy, and society, including adherence to European standards, accreditation recognition, and expanded opportunities for students and educators. This paper conducts a comprehensive analysis of recent research and publications, highlighting the need for innovation in higher education to enhance the competitiveness of Ukrainian science in the European context. The article stresses the role of HEIs in forming an innovative infrastructure that interlinks their internal structure and external relations, thereby enhancing educational outcomes. The article identifies key unresolved issues, including the systematic and purposeful process of educational innovation required for effective integration into the EEA. The paper sets objectives focused on creating conditions for seamless integration into European educational standards and approaches. It also presents a detailed analysis of the European experience in innovation, highlighting various programs and areas that aid in the integration of European higher education. Furthermore, the article discusses the negative factors impacting innovation management in Ukrainian universities due to European integration, ranging from funding discrepancies to the impact of war. Conversely, it also outlines the strengths of Ukrainian universities, such as their resilient adaptability and strong STEM foundations, which can be leveraged in the context of European integration. In conclusion, the paper argues that the integration of Ukrainian higher education into the EEA is a strategic step that requires a comprehensive and systematic approach. It calls for future research to analyze the synergies and discrepancies between European and Ukrainian educational standards and to examine international risk management practices in educational governance.